The discourse of COVID-19 vaccine in the Indonesian Ministry of Health Instagram @kemenkes_ri - Rio Satria Nugroho; Vizcardine Audinovic (Faculty of Social and Political Science, Universitas Airlangga, 2022)
The paper aims to examine how the Indonesian Ministry of Health utilizes Instagram for communicating the message regarding the COVID-19 vaccine. The widespread awareness, access, and acceptance in Indonesia of COVID-19 vaccines is a social and communication endeavor that is a highly essential consideration of spreading the messages to millions of people. The authors gathered data of Instagram posts from January 1 – May 31, 2021. The data were classified into three groups; risks and crisis information, self-efficiency and sense-making, campaign, events, and activities. The authors applied van Dijk’s critical discourse analysis concept of macrostructure, superstructure, and microstructure. The results show that the Instagram posts of the Indonesian Ministry of Health regarding the COVID-19 vaccine are classified into several sub-themes of each group. The Indonesian Ministry of Health's Instagram account uses a public information model to disseminate COVID-19 vaccination information, according to the message dissemination strategy. It applies one-way communication and indicates that the use of Instagram as a communication channel for promoting COVID-19 vaccinations has not been optimized. Another developing discourse on the Instagram account is that health workers have been prioritized and portrayed as the pandemic's hero.